2022
DOI: 10.1038/s41467-022-28517-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibody decay, T cell immunity and breakthrough infections following two SARS-CoV-2 vaccine doses in inflammatory bowel disease patients treated with infliximab and vedolizumab

Abstract: Anti tumour necrosis factor (anti-TNF) drugs increase the risk of serious respiratory infection and impair protective immunity following pneumococcal and influenza vaccination. Here we report SARS-CoV-2 vaccine-induced immune responses and breakthrough infections in patients with inflammatory bowel disease, who are treated either with the anti-TNF antibody, infliximab, or with vedolizumab targeting a gut-specific anti-integrin that does not impair systemic immunity. Geometric mean [SD] anti-S RBD antibody conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 34 publications
8
69
1
Order By: Relevance
“…In contrast, patients treated with vedolizumab were unaffected in their humoral immunity compared to healthy controls, which can be explained by the mechanism of action in targeting a gut-specific anti-integrin that does not impair systemic immunity and is in line with previous findings [ 42 ]. Furthermore, our results confirm previous studies showing attenuated vaccine efficacy in IBD patients on immunosuppressive therapies after vaccination against various other pathogens.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, patients treated with vedolizumab were unaffected in their humoral immunity compared to healthy controls, which can be explained by the mechanism of action in targeting a gut-specific anti-integrin that does not impair systemic immunity and is in line with previous findings [ 42 ]. Furthermore, our results confirm previous studies showing attenuated vaccine efficacy in IBD patients on immunosuppressive therapies after vaccination against various other pathogens.…”
Section: Discussionsupporting
confidence: 87%
“…In the study recently published by Li et al, robust T-cell reactivity was demonstrated in IBD patients on anti-TNF therapy 8 weeks after vaccination [ 48 ]. According to X et al, T-cellular reactivity was detected in approximately 80% of IBD patients receiving therapy with anti-TNF or vedolizumab at 8 to 10 weeks after COVID-19 secondary inoculation [ 42 ]. Our study was now the first to demonstrate comparable T-cell reactivity in IBD patients on immunosuppressive therapy and healthy individuals even 6 months after second SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported high seroconversion rates following two doses of either the mRNA (BNT162b2, mRNA-1273) or adenoviral vector (ChAdOx1 nCoV-19) vaccines, ranging from 81% to 100% in patients with IBD on immunosuppressive therapy (figure 3). 143–146 In one recent meta-analysis of over 9000 patients with IBD, the pooled seroconversion rate was 0.96 (95% CI 0.94 to 0.97) 147. Of 31 studies included, seroconversion rates were determined over a range of 28–179 days following a second dose of SARS-CoV-2 vaccine.…”
Section: Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…Shaded red boxes represent IBD medications with attenuated vaccine response. Figure created based on data from refs 137 143–146 154 175. using BioRender.com.…”
Section: Sars-cov-2 Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation